Problems and challenges in the implementation of Gender Mainstreaming in the Public Policy of Women of Medellín (2012-2015). A reading from meta-governance (2017)
This article examines the difficulties in the implementation of gender mainstreaming in the Public Policy of Medellin’s women, under the lens of the meta-governance literature. The purpose is to determine how the problems of coordination between actors and means of governance have influenced incorporation and implementation processes of this international strategy, within the Municipal Administration of Medellin, and especially for the period 2012-2015. For this, a review of the experiences around protocols and routes of mainstreaming within the Women's Secretariat and its Mainstreaming Team was necessary; as well as a semi-structured interview and the mainstreaming workshops which were carried out based on the project entitled “Baseline Guideline and Current Accompaniment of the Women's Public Policy for Medellin”. It was found that some of the problems and challenges of the implementation of gender mainstreaming in this period were associated to the misunderstanding of the strategy, disarticulation, and the little cooperation between the actors. Therefore, it concluded that it is necessary to continue working to ensure that the discourses around the strategy can be carried through and that more actors should join in the goal of achieving gender equality